Wir-Absichten in der individualistischen Sozialontologie - Bühler, Axel; Justus Liebig University Giessen (My University, 2009)
An individualistic social ontology attributes mental states merely to individuals, and denies the existence of collective attitudes such as we-intentions. Furthermore, if collectives cannot be bearers of minds, then collective mental states cannot serve as explanatory factors. In my paper, I first show that we-intentions do serve considerable explanatory purposes within developmental psychology. I then propose an account of weintentions as complexes of intentions of different individuals. These intentions are of a distinct kind: de-re-intentions, grounded in external objects in a specific situation. This grounding is achieved by embodied cognition, through appropriate senso-motoric activities. I conclude that my account of we-intentions is compatible with an individualistic social ontology.
Keywords: ddc:100; ddc:330